Cytotoxicity and cell cycle arrest induction by acetone banana peels extract on human skin cancer A375 and human leukemia HL-60 cell lines - Mohammed, Fadia Hameed; Hassan, Walaa Salih; Al-Saily, Hala M.N.; Yazi Abdullah (Edelweiss Applied Science and Technology, 2025)
Today, modern medicine has started to rely on phytoremedies for obtaining safe drugs, particularly for targeting cancer cells. Banana peels are packed with many pharmacologically interesting phytochemical compounds, and research is needed to investigate their anti-cancer activity. Banana peel was extracted using 50% acetone and then analyzed for its antioxidant activity using the DPPH assay, as well as for the presence of some anticancer compounds through HPLC analysis. The cytotoxicity of the banana peel extract on human skin cancer A375 and human leukemia HL60 cell lines was studied via the MTT assay and cell cycle arrest analysis. The results revealed a strong antioxidant potency of the banana peel extract, with an IC50 of 20.85 ppm in the DPPH assay. HPLC analysis revealed the presence of dopamine, quinic acid, and chlorogenic acid in concentrations of 42.65, 74.59, and 42.65 µg/ml, respectively. The MTT assay showed that mesenchymal cells had an IC50 of 746.8 µg/ml and remained viable, while A375 cells had an IC50 of 269.27 µg/ml, and HL60 cells had an IC50 of 317.68 µg/ml, both showing significant declines in viability. The findings of the cell cycle arrest demonstrated that the cell cycle of A375 cells was halted in the G1 and S phases at a concentration of 400 g/ml of banana peels. The extract exhibits strong antioxidant potency and high cytotoxicity for human skin cancer A375 and human leukemia HL60 cell lines, but A375 cells were more sensitive to the extract, while normal mesenchymal cells were not affected.